Affective dysregulation and sex differences in somatic symptom disorder: A 6-month longitudinal and mediation analysis - Yuna Jang; EKyong Yoon; Arum Hong; Hye Youn Park (Comprehensive Psychiatry, 2025)
Objectives: Somatic symptom disorder (SSD) is characterized by persistent physical symptoms and excessive emotional responses, but the influence of emotional factors such as anger and alexithymia on symptom severity and course remains unclear. This study examined whether baseline levels and six-month changes in emotional factors are associated with somatic symptom severity and course in SSD, considering sex. Methods: Eighty-three SSD patients and 80 age- and sex-matched healthy controls completed self-report measures of emotional and somatic symptoms at baseline and six-month follow-up. Changes in symptom levels were compared between patients and controls. Emotional factors associated with symptom severity and change were also examined. Linear mixed models, multiple regression, and Bayesian mediation analyses were employed. Results: Compared to controls, the SSD group showed significant improvement in somatic symptoms over six months. Trait anger was significantly associated with somatic symptom severity in females, and an interaction between anxiety and trait anger predicted symptom severity. Within the SSD group, reductions in anxiety and alexithymia were significantly associated with symptom improvement. Mediation analyses supported indirect pathways between affective change and symptom reduction. Conclusions: This prospective study highlights the contribution of emotional dysregulation to both the severity and course of somatic symptoms in SSD. The findings emphasize the relevance of sex differences and emotion-focused mechanisms in symptom maintenance and improvement, supporting the need for tailored interventions in SSD treatment.